Sleep Bruxism and Obstructive Sleep Apnea – Shared Pathophysiology or Coincidence? - Marcjasz, Piotr; Bioły, Anna; Buliszak, Agnieszka; Babczyńska, Monika; Chodkowska, Ewa; Bielas, Kinga (Quality in Sport, 2025)
Introduction: Sleep bruxism (SB) is a jaw-muscle activity during sleep while obstructive sleep apnea (OSA) is a disorder of recurrent upper airway collapse during sleep [5, 1]. Recent research has noted frequent co-occurrence of SB in OSA patients. Aim: This narrative review examines the relationship between SB and OSA to determine if SB and OSA share underlying mechanisms or simply coexist by chance. Materials and Methods: A literature review was conducted using the databases such as Pubmed and Google Scholar. State of knowledge: SB was prevalent in about one-third to one-half of OSA patients across studies [5, 6]. Mild-moderate OSA is associated with significantly higher SB activity than severe OSA [6, 12]. Both conditions share risk factors, and OSA itself has been identified as an independent risk factor for SB [6, 3]. Notably, treating OSA can lead to significant reductions in SB episode frequency [15, 11]. Conclusions: SB and OSA frequently co-occur and exhibit intertwined pathophysiology in certain patients. Awareness of this association is important: OSA may be one of the most frequent modifiable triggers of SB [6], and treating OSA can alleviate SB in those cases [11, 13]. An interdisciplinary approach involving dentists and sleep physicians is recommended to identify and manage coexisting SB and OSA [14].